Evaluation of the implementation of South-South cooperation between Brazil and São Tomé and Príncipe in the Cardoso, Lula and Rousseff governments - Violante, Alexandre Rocha; Pedone, Luiz (Faculdade de Filosofia e Ciências, 2021)
The Cardoso, Lula and Rousseff governments presented, except for their political and strategic peculiarities, the South-South Cooperation policy as one of the bases for insertion in the international system. Based on the objectives and goals of foreign policy, the high-level documents of National Defense and the cooperation agreements with São Tomé and Príncipe, projects, actions and activities were established that aimed at highlighting the Brazilian leadership in the South Atlantic, increasing the hard power of bias both states and promote security in the region. The choice for this State was due to its location in the Gulf of Guinea – a privileged area for living and non-living resources, such as large oil basins, but subject to the so-called “new threats” and the greed of States with greater regional and extra-regional relative power. The hypothesis is that public intervention proved to be a failure in its execution, being dependent on the internal and external conjunctures of each country (mainly from Brazil). Thus, this article's main objective is to evaluate the implementation of the Brazilian South-South Cooperation program with São Tomé and Príncipe from 1995 to 2016, through the methodology of public policies of Evert Vedung, using intervention theory, an effectiveness model aimed at achieving its goals, illustrating stakeholders and evaluating eight problems. identifying the gaps that hindered the achievement of this power project. Finally, the gaps that hindered the achievement of this power project by the Brazilian State in the period were identified.